Some Results for the (Signless) Laplacian Resolvent - Cafure, Antonio Artemio (2017)
The recently introduced concept of resolvent energy of a graph [6,7] is based on the adjacency matrix. We now consider the analogous resolvent energies based on the Laplacian and signless Laplacian matrices, and determine some of their basic properties.